ANALISIS PEMIKIRAN EKONOMI AL-GHAZALI - Adelia, Putri; Khoiriyah , Zainab (CV. Pusdikra Mitra Jaya, 2025)
According to al-Ghazali, the goal of a Muslim's life is to attain Allah's blessings (ridha) both in this world and the next. One of the means that facilitates this achievement is legal wealth (halal) in economic activities. For al-Ghazali, the market is believed to be an evolution of